10 Genetic associations with brain microbleeds: systematic review and meta-analyses. Issue 3 (15th February 2011) - Sudlow, C L M; Maxwell, S S; Jackson, C A; Paternoster, L; Cordonnier, C; Thijs, V; Salman, R A S
Abstract : Introduction: The frequency of brain microbleeds (BMBs) increases with age, and with a history of hypertension, smoking and stroke (particularly intracerebral haemorrhage), but genetic associations with BMBs are less clear. Methods: We sought all published studies of the association between any genetic polymorphism and BMBs studied in a total of >100 people. We critically appraised studies, and calculated pooled odds ratios (ORs) using the generic inverse variance fixed effects method. We used I2 and X2 statistics to assess heterogeneity, and failsafe N estimates to assess the robustness of our results. Results: Only the apolipoprotein E (APOE) ε2/3/4 polymorphism had been studied in >100 people (10 studies, 4, 662 participants). Compared with people with the ε3/ε3 genotype, carriers of the ε2 or ε4 allele (ε2+, ε4+) were statistically non-significantly more likely to have BMBs in any location (ε2+ vs ε3/ε3: pooled OR 1.28, 95% CI 1.00 to 1.63, p=0.05; ε4+ vs ε3/ε3: pooled OR 1.20, 95% CI 0.99 to 1.44, p=0.06). For strictly lobar BMBs, these associations were stronger and statistically significant (ε2+ vs ε3/ε3: pooled OR 1.51, 95% CI 1.05 to 2.18, p=0.03; ε4+ vs ε3/ε3: pooled OR 1.56, 95% CI 1.17 to 2.08, p=0.003). The effects of the ε4 allele were robust to potential publication and reporting biases. Conclusions: Given the known associations of APOE alleles with lobar intracerebral haemorrhage and cerebral amyloid angiopathy, these findings support the concept that strictly lobar BMBs may be an imaging biomarker of cerebral amyloid angiopathy. Genome-wide association studies may identify other genetic influences.